Penyuluhan Hukum : Pendirian Dan Pemberdayaan Bum Desa Mendak Kecamatan Dagangan Kabupaten Madiun - Sigit Sapto Nugroho; Mudji Mudji Raharjo; Hirman Hirman (JURNAL DAYA-MAS, 2019)
The purpose of this community service is to provide counseling and dissemination of the establishment of Village-Owned Enterprises (BUM Desa) with all formal legal aspects and the development of BUM Desa empowerment. Including Mendak Village, Dagangan Subdistrict, Madiun Regency, which has the potential of superior products in the form of fruit plants and natural tourism potential such as Watu Rumpuk tourist destinations. The implementation of community service is carried out by using methods of counseling or legal communication both directly and indirectly.Referring to the laws and regulations the establishment of BUM Desa as a village economic institution must have a strong legal basis. Where the BUM Desa privilege is located in 1) the formation of sufficient Perdes, 2) the highest authority in the hands of the Musdes, 3) ownership of at least 60% of the village government. These three things are to maintain the sovereignty of the establishment and management of BUM Desa in the hands of the villagers. There are three factors that influence the success of BUM Desa. First, natural resources owned. The second factor is funding capital for financing. Third, the factor of Human Resources (HR).